2017
DOI: 10.5304/jafscd.2017.074.008
|View full text |Cite
|
Sign up to set email alerts
|

Oregon producer and consumer engagement in regional food networks: Motivations and future opportunities

Abstract: Local and regional food marketed through direct and intermediated channels has been increasing in the U.S., with studies of producers and consumers conducted at different places and times illuminating the trend. Oregon producers and consumers have shown long-running interest in local agriculture, with direct markets providing a wellestablished connection between fresh and local food. To examine motivations and barriers for the continued development of the Oregon regional food network (RFN), we conducted in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…That a general divide does exist is further supported by a recent Oregon producer survey which found that value‐based motivations for choosing production practices were correlated in expected ways with self‐reported conventional or alternative practices. However, the survey also found that other factors such as access to markets and local or regional support also influence the practice decisions of farmers regardless of style (Brekken, Parks, and Lundgren ).…”
Section: Discussionmentioning
confidence: 96%
“…That a general divide does exist is further supported by a recent Oregon producer survey which found that value‐based motivations for choosing production practices were correlated in expected ways with self‐reported conventional or alternative practices. However, the survey also found that other factors such as access to markets and local or regional support also influence the practice decisions of farmers regardless of style (Brekken, Parks, and Lundgren ).…”
Section: Discussionmentioning
confidence: 96%
“…The interviews revealed some significant differences by size of operation, which is important because a vibrant DM sector that sells products through a range of marketing channels is composed of a mix of small to large producers that can satisfy diverse consumer demands [19]. The mid-sized producers who reported the greatest pressure from the MW increase perceive themselves as having little pricing power, and anticipate making more modifications to their operations than producers in the other size categories.…”
Section: Discussion: Impacts Of the Minimum Wage Increasementioning
confidence: 99%
“…In another recent Oregon producer survey, the farmers who indicated that they used various environmentally-sensitive production practices were also much more likely to indicate that they chose their production practices because they "align" with their environmental values [19].…”
Section: Discussion: Impacts Of the Minimum Wage Increasementioning
confidence: 99%
See 2 more Smart Citations